2013
DOI: 10.1016/j.bone.2013.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Bone cysts after osteochondral allograft repair of cartilage defects in goats suggest abnormal interaction between subchondral bone and overlying synovial joint tissues

Abstract: The efficacy of osteochondral allografts (OCA) may be affected by osseous support of the articular cartilage, and thus affected by bone healing and remodeling in the OCA and surrounding host. Bone cysts, and their communication pathways, may be present in various locations after OCA insertion and reflect distinct pathogenic mechanisms. Previously, we analyzed the effect of OCA storage (FRESH, 4°C/14d, 4°C/28d, FROZEN) on cartilage quality in fifteen adult goats after 12 months in vivo. The objectives of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 47 publications
1
40
1
3
Order By: Relevance
“…It is well known that chondrocyte viability diminishes when grafts are stored at 4 C after 28 days. 28 More recent studies have reported better results storing grafts at 37 C or room temperature. [20][21][22][23][24][25][26] These findings would lead to the potential of the allografts tolerating a longer storage time, but other factors need to be taken into consideration such as the risk of infection.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is well known that chondrocyte viability diminishes when grafts are stored at 4 C after 28 days. 28 More recent studies have reported better results storing grafts at 37 C or room temperature. [20][21][22][23][24][25][26] These findings would lead to the potential of the allografts tolerating a longer storage time, but other factors need to be taken into consideration such as the risk of infection.…”
Section: Discussionmentioning
confidence: 98%
“…The importance of subchondral bone has been investigated by Pallante-Kichura et al, 28 determining the effect of osteochondral storage on subchondral bone, characterizing the structure and location of bone cysts found in subchondral bone after osteochondral grafting, and assessing the relation between cartilage and bone after an allograft transplantation. Frozen allograft exhibited eroded subchondral bone, all allografts contained basal cysts, and subchondral bone pathology was related to overlying articular cartilage integrity.…”
Section: Large Fresh Osteochondral Allograft Of Kneementioning
confidence: 99%
See 1 more Smart Citation
“…10,11,[46][47][48] The long-term impact on the loss of mechanical integrity at this interface and the ability of fluid to penetrate into the underlying bone is an area of ongoing research. 51 Finally, we included an experimental TE group in this study, in which we filled the defect with an HA hydrogel. This is a base material that our group and others has used as a cell-delivery vehicle and scaffold for cartilage TE.…”
Section: Focal Cartilage Repair and Bone Remodeling In Pigsmentioning
confidence: 99%
“…Through these in vivo animal studies, we determined (1) at 6 months, frozen OCA already exhibited clear progression toward failure, with loss of chondrocytes, reduced proteoglycan content and cartilage stiffness, and associated surface and/or bone collapse, while fresh OCA preserved depth-dependent tissue properties similar to non-operated cartilage, and thus maintained their capacity for biological homeostasis 19 ; (2) proteoglycan-4 (PRG4)secreting function of OCA is maintained based on its state at implantation 20 ; (3) frozen OCA show similar changes at 12 months that were evident after 6 months whereas 4˚C stored OCA exhibit reduced performance and variable long-term outcomes which were associated with reduced cellularity at the articular surface versus consistently good repair by fresh OCA 18 ; (4) the presence of bone cysts (void areas diameter greater than 1 mm by mCT) were widespread and bone structure was altered by OCA relative to contralateral non-operated control knees 21 ; and (5) OCA repair patterns all exhibited basal cysts (located near the base of the implant), and occurred (a) in isolation, (b) with subchondral cysts (located near the bone-cartilage interface) and subchondral bone (ScB) channels, (c) with ScB channels, or (d) with subchondral cysts, ScB channels, and ScB erosion suggesting that bone cysts occurring after OCA may result from aberrant mechanobiology. 21 Current MRI grading scales used for cartilage repair or osteoarthritis are not targeted to evaluate OCA repair that have both chondral and osseous components. Thus, we were motivated by the need for non-invasive characterization of OCA and the ability to refine MRI technology to predict clinical outcomes.…”
Section: Biological and Structural Aspects Of In Vivo Cartilage And Bmentioning
confidence: 99%